The Twisted Politics of History in Putin’s Russia: Approach to German-Soviet Non-Aggression Pact of 23 August 1939 - Vyšniauskas, Arūnas (Genocidas ir rezistencija, 2022)
Although the politics of history in Putin’s Russia has already become a topic of scientific research internationally, the twists and turns of this policy in the interpretation and assessment of the so-called Molotov-Ribbentrop Pact throughout Putin’s reign have not yet been sufficiently examined. The article attempts to fill this gap, at least in part, by drawing on publicly available sources. It provides a concise account and analytical framework of developments in Russian historical politics between 1999 and 2021 in the treatment of the 1939 German-Soviet non-aggression treaty, also known as the Hitler-Stalin or Molotov-Ribbentrop Pact. Although the Second Congress of People’s Deputies of the USSR on 24 December 1989 condemned the secret agreements between the Soviet Union and Nazi Germany, after the collapse of the USSR, the Ministry of Foreign Affairs of the Russian Federation made the first attempt to re-justify the 1939 non-aggression treaty with Nazi Germany as early as in 1999. During the long period of Putin’s rule, the tendency to justify the Molotov-Ribbentrop Pact and its secret additional protocol, and the USSR’s territorial expansion of 1939–1940, has been growing, especially after Russia’s annexation of Crimea in spring 2014. The Kremlin’s historical narrative portrays the pact as an episodic phenomenon, not very moral, but justified in terms of Russia’s geostrategic interests, avoiding to emphasise that the partition of Europe based on the secret agreements was at the expense of the sovereignty of smaller states. However, the history of the 22-month alliance and collusion between the Soviet Union and the German Reich between 1939 and 1941 has been and continues to be a problem for the Kremlin, particularly internationally. This may explain the vacillation (manoeuvring) of the official position with regard to treatment of the Molotov-Ribbentrop Pact and the subsequent agreements with Nazi Germany that followed from it. In recent years, especially since 2018, Moscow’s official history policy strategy has given a special role to the work of Russian archives in making previously classified sources publicly available online. The aim is to document the complexity and intricacy of the international situation on the eve of and during the Second World War, which, from Moscow’s point of view, can contribute to breaking the anti-Soviet and anti- Russian propaganda clichés that are unfavourable to it, and to rejecting the primitive speculations about the causes and consequences of the Molotov-Ribbentrop Pact. At the same time, the aim is to remind everyone that other countries (USA, UK, France, and even Poland) had shameful deals with Hitler’s Germany or made mistakes in their relations with it. In this context, it is important to further investigate the politics of history in Russia and to analyse it in a broader context, taking into account the changes taking place, and to include other countries’ approaches to historical politics and their evolution in the interpretation of the causes, origins, and the initial stages of the Second World War.